Zmiany organizacyjno-prawne przedsiębiorstwa państwowego w okresie Polskiej Rzeczypospolitej Ludowej - Kostecka-Jurczyk, Daria (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In Poland, during the People’s Republic of Poland, the policy of central management of the economy was based on the principles of unity of state power and unity of state property. They constituted the foundation of the state sector and the state economic activity. State-owned enterprises, strongly subordinated to public administration bodies, were the leading form of economic activity. The authoritarian state controlled not only the process of enterprise creation, liquidation and supervision, but also the enterprises’ operational activities. Strong state supervision and lack of responsibility for financial results were the main reasons for their low profitability, which in turn brought about attempts to reform the legal structure of the state-owned enterprises. The aim of the article is to show the legal and organizational changes in state-owned enterprises that are to produce an increase in economic efficiency. Based on the historical-legal method and the grammatical interpretation of the law, it was shown that the reforms undertaken in the field of the organization of state-owned enterprises were not effective.
Keywords: przedsiębiorstwo państwowe; gospodarka nakazowa; działalność gospodarcza państwa autorytarnego; gospodarka centralnie planowana; nadzór założycielski; własność państwowa